Effects of supplementation of Bacillus amyloliquefaciens on performance, systemic immunity, and intestinal microbiota of weaned pigs experimentally infected with a pathogenic enterotoxigenic E. coli F18 - Jinno, Cynthia; Wong, Braden; Klünemann, Martina; Htoo, John; Li, Xunde; Liu, Yanhong (Frontiers in Microbiology, 2023)
The objective of this study was to investigate the effects of supplementation of Bacillus (B.) amyloliquefaciens on growth performance, diarrhea, systemic immunity, and intestinal microbiota of weaned pigs experimentally infected with F18 enterotoxigenic Escherichia coli (ETEC). Fifty weaned pigs (7.41 ±1.35 kg BW) were individually housed and randomly allotted to one of 5 treatments: sham control (CON-), sham B. amyloliquefaciens (BAM-), challenged control (CON+), challenged B. amyloliquefaciens (BAM+) and challenged carbadox (AGP+). The experiment lasted 28 days with 7 days of adaptation and 21 days after the first ETEC inoculation. ETEC challenge reduced (P < 0.05) average daily gain (ADG) of pigs. Compared with CON+, AGP+ enhanced (P < 0.05) ADG, while B. amyloliquefaciens supplementation tended (P < 0.10) to increase ADG of pigs from d 0 to 21 post-inoculation (PI). ETEC challenge increased (P < 0.05) white blood cell (WBC) count on d 7 and 21 PI, while BAM+ pigs tended (P < 0.10) to have low WBC on d 7 PI and had lower (P < 0.05) WBC on d 21 PI compared with CON+. In comparison to AGP+ fecal microbiota, BAM+ had lower (P < 0.05) relative abundance of Lachnospiraceae on d 0 and Clostridiaceae on d 21 PI, but higher (P < 0.05) relative abundance of Enterobacyeriaceae on d 0. In ileal digesta, Shannon index was higher (P < 0.05) in BAM+ than AGP+. Bray-Curtis PCoA displayed difference in bacterial community composition in ileal digesta collected from sham pigs vs. ETEC infected pigs on d 21 PI. Pigs in BAM+ had greater (P < 0.05) relative abundance of Firmicutes, but lower (P < 0.05) relative abundance of Actinomycetota and Bacteroidota in ileal digesta than pigs in AGP+. Ileal digesta from AGP+ had greater (P < 0.05) abundance of Clostridium sensu stricto 1 but lower (P < 0.05) Bifidobacterium than pigs in BAM+. In conclusion, supplementation of B. amyloliquefaciens tended to increase ADG and had limited effects on diarrhea of ETEC infected pigs. However, pigs fed with B. amyloliquefaciens exhibit milder systemic inflammation than control. B. amyloliquefaciens differently modified intestinal microbiota of weaned pigs, compared with carbadox.